Vorticity budget over mountains, estimated from HIRLAM analyses and forecasts - Laura Rontu (Meteorologische Zeitschrift, 2006)
The analysis of vorticity budgets offers a possibility for validation and diagnosis of a NWP model. The source terms of the equation are related to the resolved and subgrid-scale torque due to the orography and surface properties. In this study, the vorticity method was applied to the diagnosis of High Resolution Limited Area Model (HIRLAM). The terms resolved by the model were estimated from three-dimensional numerical analyses and forecasts. In the vertically integrated equation, these terms sum up to give an estimate of required torque due to the subgrid-scale surface stress, which was compared with the corresponding value given by the physical parametrizations of the model. The magnitude of the parametrized subgrid-scale torque was about a half of that derived from the integrated vorticity budget. Diagnosis of the complicated terms of the equation requires special attention to the discretization and numerical approximations. A detailed discussion of the advantages and disadvantages of the method is included.